Design of a passive wearable device using an optimized mechanical metamaterial for mirror therapy - Raghavendra Kulkarni, Suhas (2024)
Mirror Therapy (MT) is an effective therapeutic method used in the rehabilitation of hemiplegics. The effectiveness of this method is improved by employing a bi-modal approach which requires the synchronous movement of the affected and unaffected arm. For this purpose, we describe the design of a wearable device using a Mechanical Metamaterial (MM) that is optimized for the specific user to provide passive assistance of wrist flexion-extension and enable synchronous motion of the affected and unaffected arm during MT.